Implementation of the Institute for a Class Action to the Legislation of Ukraine in the Context of Approximation to the Standards of the European Union - PRYTYKA, Yurii D. (Journal of Advanced Research in Law and Economics, 2019)
The urgency of the study is conditioned by the rapid development of the institution of collective action in European law and the necessity to adapt domestic civil procedural law to EU law. At the same time, the choice of a correct and effective system of protection of rights, freedoms and interests should be made with consideration of the national legal traditions and peculiarities of the national legal system. In particular, this also applies to ‘mass’ infringement of rights, the optimal protection of which in European law is linked to the institution of collective action. In the above context, the important prerequisite for the implementation of the collective action institute in domestic law is the doctrinal definition of such a collective action model, which allows to take into account both the necessity for adaptation of EU civil procedural law and the already established domestic procedural doctrine. Given the flexibility of the approach to the unification of the collective action institute model in different EU countries and the different legal constructs in the field of collective rights protection, which will be investigated further, it is logical to define such a legal mechanism that is: (1) most closely approximated to national procedural structures; and (2) effective in modern domestic legal and social conditions. Therefore, the purpose of the article is to investigate the general tendencies of the development of a class action lawsuit and to identify a specific legal model of a class action lawsuit that can be implemented in the national legislation of Ukraine.